Josep Cuatrecasas. A secretis redactor [Cavanillesia, 1928-1938] - González Bueno, Antonio (Mediterranean Botany, 2022)
We analyze the activity of Josep Cuatrecasas Arumí (1903-1996) as editorial secretary of the magazine Cavanillesia, published between 1928 and 1938. We value his participation from four fronts: secretary, author, reviewer and re-rated. The study allows specifying the date of publication of the articles in the journal, the influence of Emili Huguet del Villar on the geobotanical methodology followed by Josep Cuatrecasas and his effort to disseminate the new botanical publications, from the pages of the journal, together with Pius Font i Quer.